Pengembangan Strategi Pembelajaran Model Dick and Carey Pada Materi Laju Reaksi Fase F SMA - Astari, Besse Firanita; Djono, Djono (Arfak Chem: Chemistry Education Journal, 2024)
The Dick and Carey model is a learning-development model. Each step in the model is systematic and sequential. There are ten steps explained by Dick and Carey, and in this article, the focus is on the sixth step, namely developing learning strategies. The educator, in this case, must design an effective strategy for every learning process to ensure it effectively achieves the expected goals. This article examines various relevant literature as a foundation for designing chemistry learning as a reference for the development of chemistry students, for example, in high school F-phase reaction rate material. The results of the development of the Dick and Carey model learning strategy on reaction rate material show the components of teaching, testing, and follow-up of the learning strategy. In addition, constructivism incorporates learning strategies as an integral part of its teaching methodology. This article provides a complete understanding of designing learning strategies specifically for chemistry subjects using the Dick and Carey model